1994
DOI: 10.1104/pp.104.4.1401
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Low Molecular Mass Autophosphorylating Protein in Cultured Sugarcane Cells and Its Identification as a Nucleoside Diphosphate Kinase

Abstract: A low molecular m a s (18 kD) phosphoprotein (pp18) was characterized and purified from cultured sugarcane (Saccharum officinarum 1.) cell line H50-7209. Autophosphorylation assays were used to detect pp18 after separation by sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PACE). Only pp18 was detected by a brief in situ phosphorylation method, whereas additional putative protein kinases were detected by an extended method. pp18 was present in both microsomal membrane and soluble fractions and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 27 publications
1
28
0
4
Order By: Relevance
“…The low-molecularmass 16-kD putative NDPK form detected in the soluble and membrane protein fractions from wheat tissues could be related to the 16-kD form previously described (Nomura et al, 1992;Finan et al, 1994) and to the 18-kD NDPK from sugarcane cells (Moisyadi et al, 1994). The wheat immature embryos revealed a reduced amount of the 16-kD membrane form compared with in vitro-cultured cells.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…The low-molecularmass 16-kD putative NDPK form detected in the soluble and membrane protein fractions from wheat tissues could be related to the 16-kD form previously described (Nomura et al, 1992;Finan et al, 1994) and to the 18-kD NDPK from sugarcane cells (Moisyadi et al, 1994). The wheat immature embryos revealed a reduced amount of the 16-kD membrane form compared with in vitro-cultured cells.…”
supporting
confidence: 51%
“…The enzyme from eukaryotes is a hexamer of identical subunits with a particular mononucleotide binding fold (Dumas et al, 1992). A striking homology of the amino acid sequence of spinach NDPK with both the human and Drosophila melanogaster NDPKs was established (Nomura et al, 1992;Moisyadi et al, 1994). This led to the hypothesis of a possible contribution of the NDPK protein to the development of plant tissue, including cell proliferation, through signaltransduction pathways (Wallet at al., 1990).…”
mentioning
confidence: 99%
“…A possible regulatory function remains conceivable given the abundant expression of NDPK/Nm23 in many tumor tissues [39, 401. Further evidence for the existence of a Nm23 protein phosphotransferase activity in the cell is provided by several reports on NDPK from plants, which all show a high degree of sequence similarity to human NDPK 1411. It was reported that NDPK may act as a kind of active subunit of protein kinase complexes in pea [42,43] and sugar-cane [44]. The NDPK preparations apparently exhibited a weak serine phosphotransferase activity toward membrane proteins, which could be stimulated by Ca' ' and calmodulin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, plant NDP kinases have been proposed as a part of the signal transduction pathway during stress (92). NDP kinase from cultured sugarcane cells exhibits heat shock-stimulated autophosphorylation activity (93), and in tomato plant, its mRNA level is up-regulated in response to wounding (94). Since one of the most common signal transduction events during heat shock is protein phosphorylation, the up-regulated NDP kinase activity and protein levels may allow the plant to perceive and transduce signals related to high temperature stress (92).…”
Section: Discussionmentioning
confidence: 99%